Industrial uses of biomass energy the example of Brazil - Rosillo-Calle, Francisco 1945-; Bajay, Sergio Valdir; Rothman, Harry (Routledge, Taylor & Francis Group, 2019)
Industrial Uses of Biomass Energy demonstrates that energy-rich vegetation, biomass, is a key renewable energy resource for the future. Brazil, uniquely, has a recent history of large-scale biomass industrial uses that makes it a specially important test-bed both for the development of biomass technology and its utilisation, and for understanding how this is shaped by political and socio-economic forces. The book analyses the cause for this and the alternatives. It is argued that Brazil's experience with the development for industrial biomass use provides wider lessons and insights in the context of the international movement for sustainable economic development.This book is an interdisciplinary, multi-author work, based upon a recently completed international study by Brazilian and British experts and will prove a valuable reference to all those working in this field